Peningkatan Kemampuan Membaca Pemahaman Cerita Pendek dengan Strategi Pembelajaran Directed Reading Thinking Activity (DRTA) pada Siswa Kelas V SD GMIT Airnona 2 Kota Kupang - Mamulak, Prisila Apriani; Sampe, Markus; Devi, Rista Apriliya (Lembaga Yasin AlSys, 2025)
Reading comprehension is a fundamental skill essential to supporting students’ academic success. Based on observations at SD GMIT Airnona 2 in the city of Kupang, it was found that fifth-grade students experienced difficulties in understanding short stories, particularly in identifying intrinsic elements and summarizing story content, even after repeated readings. This study aims to improve short story reading comprehension through the application of the Directed Reading Thinking Activity (DRTA) strategy. The research employed a classroom action research method in two cycles, involving 26 fifth-grade students, and combined both qualitative and quantitative approaches. Data collection techniques included observation, interviews, tests (pretest and posttest), and documentation study. The results showed that the implementation of the DRTA strategy significantly improved students’ reading comprehension abilities. The percentage of learning mastery increased from 19.2% in the pre-cycle to 57.7% in the first cycle and reached 100% in the second cycle. The students’ average scores also increased from 69.4 to 80.8, accompanied by improvements in teacher activity and student engagement during the learning process. These findings indicate that the DRTA strategy can be an effective instructional approach to address low reading comprehension among elementary school students and is recommended as an alternative method in literacy instruction.